Study Of Inhomogeneous Dielectric Resonators For Linearly Circularly Polarized Microwave Antenna Applications - ULLAH, UBAID (2016)
In the last three decades a huge amount research has been dedicated to homogeneous (single permittivity) dielectric resonators (DRs) with cylindrical, rectangular/square and hemispherical shapes being the center of attention. These DRs have been investigated theoretically, numerically, and experimentally therefore, all the major performance controlling parameters are known for the homogeneous DRs. It well known that a homogenous DR can serve only one purpose at a time i.e. strong coupling to the source and hence narrow impedance bandwidth and vice versa. To overcome these drawbacks of homogenous DRs, in this work inhomogeneous DRs are designed in such a way that the basic geometry of the resonator is maintained so that the available theoretical, numerical and experimental analysis tools can be effectively applied to the proposed inhomogeneous DRs. The inhomogeneities in the resonators are introduced systematically in the azimuth (ϕ) direction so that the electromagnetic field distribution in the resonators remains the same with different range of energy confinement. To validate these ideas three different resonators based on cylindrical dielectric resonator (CDR) and rectangular/square shape resonators are investigated. For inhomogeneous CDR two 90ᴼ pie shape sectors of relatively high permittivity were introduced in the ϕ-direction in a way that sectors with same permittivity are placed in the opposite quadrant. Similarly, another inhomogeneous DR (split-oval shape) was designed by inserting high permittivity rectangular strip in the middle of two half cylindrical DR in the ϕ direction. Lastly, the third design of this research is based on a square shape DR in which the permittivity is lowered by introducing air-gap within the resonator which appears like a nested square DR. The proposed inhomogeneous DRs are tested for linearly polarized (LP) wideband antenna applications with a common excitation technique i.e. microstrip line. While, for circularly polarized (CP) designs, it is important to excite two orthogonal modes with the same amplitude hence different feeding techniques are used. Theoretical, numerical and experimental analysis of the inhomogeneous dielectric resonator antennas (DRA) showed that by properly designing inhomogeneous resonators, impedance bandwidth response, axial ratio (AR) bandwidth, gain and efficiency of the DRA‘s can be improved. For all three inhomogeneous LP DRA‘s approximately 56% impedance bandwidth was achieved which shows 80.5% enhancement of bandwidth over homogeneous DRAs with stable radiation characteristics throughout the operating band. The AR bandwidth response of the CP inhomogeneous DRA‘s was recorded to be 200% more than that of homogeneous counterparts. For the first two inhomogeneous DRAs gain was improved up to 6.5 dBi while for the nested square DR gain remained almost the same as that of the homogeneous square DR. With reference to these findings it was found that performance of the DRA can be noticeably improved with systematic introduction of inhomogeneity in the DR.